Efektivitas Model Pembelajaran Creative Problem Solving Berbantuan Alat Peraga Manipulatif Terhadap Hasil Belajar Siswa SMP - Virda, Diah Royanul; Rahmawati, Noviana Dini; Endahwuri, Dhian (Universitas PGRI Semarang, 2026)
The study was conducted to determine the effectiveness of the Creative Problem Solving learning model assisted by manipulative teaching aids on the learning outcomes of junior high school students. The research method used is quantitative with a research design in the form of a posttest-only control design. The study was conducted at SMP Negeri 1 Bangsri with sampling using the cluster random sampling technique on class VIII students. The sample consisted of two class, namely class VIII C as an experimental class tha would be given treatment in the form of the application of the Creative Problem Solving learning model assisted by manipulative teaching aids and class VIII D as a control class that would be given treatment in the form of the application of conventional learning models. Data collection techniques in the form of tests given after the treatment. Based on the effectiveness indicators, there are three assessments in this study, namely the difference in learning outcomes of the experimental class and the control class, a better comparative test, and the completeness of learning outcomes in the experimental class. The final data were analyzed using the Independent Sample T-test that there were difference in learning outcomes of students in the experimental class and the control class. Then for the comparative test of the experimental class and the control class, the One-Party T-test formula was used by showing that the experimental class was better than the control class. The learning outcomes of the experimental class reached an average value of 78 with 25 students achieving individual completeness and 5 students who did not complete it. So it can be said that the completeness of student learning in the experimental class classically can be said to be complete because it achieved completeness of 83%.